Students’ experiences on occupational therapy clinical placement : a narrative review - Dzalani Harun,; Hanif Farhan Mohd Rasdi,; Aimi Najihah Abdul Razak, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Clinical placement practice is the most significant part of occupational therapy education. It is a place where students can observe and experience how theory and practical understanding are helpful in the real world. This review aims to identify the common experiences of occupational therapy students during their clinical placement. Findings of this study can provide a better understanding of student’s experiences and improve the current clinical placement practice. Methods: This is a narrative review study. Literature searches on English language articles only were conducted on relevant databases, including EBSCOhost, Academic Search Complete, Academic Search Premier, Education Resources Information Center (ERIC) and MEDLINE within the year 2007 until 2018. The final numbers of selected studies were 11. Results and Discussion: Three themes emerged from this review: (1) skills developed during clinical placement refers to students’ understanding of occupational therapy role and ability to integrate academic knowledge into practical skill and to develop clinical core skills, (2) the supervisor’s role during clinical placement, which describes the responsibility of supervisors to establish the student-supervisor relationship, provide feedback to students, and shape students’ attitudes and (3) the challenges that arise during clinical placement, which refer to issues faced by the students during their clinical placement. Conclusion: Students have gained valuable experiences and learning opportunities that directly impacted their professional training. The specific features of clinical placement, including theoretical knowledge, practical skills, clinical reasoning, communication skills and interaction with supervisors and peers, were the definite aspects influencing students’ essential competencies.